Pengaruh Profitabilitas, Kualitas Laba Dan Keputusan Investasi Terhadap Nilai Perusahaan - Reza Refki Tanggo; Salma Taqwa (Universitas Negeri Padang, 2020)
The purpose of this study was to analyze: (1) The effect of profitability on firm value. (2) The effect of earnings quality on firm value. (3) The effect of investment decisions on firm value. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. While the sampling technique in this study is using purposive sampling technique with a total sample of 300 samples. The data analysis method used is multiple regression using SPSS 25 software. The results of this study indicate that: (1) profitability has a positive and significant effect on firm value with a significance of 0.000 < 0.05. (2) earnings quality has a positive and insignificant effect on firm value with a significance of 0.757 > 0.05. (3) investment decisions have a positive effect and not on the value of the company with a significance of 0.418 > 0.05